2022
DOI: 10.3389/fpsyt.2022.976428
|View full text |Cite
|
Sign up to set email alerts
|

Association between variants of MTHFR genes and psychiatric disorders: A meta-analysis

Abstract: BackgroundPsychiatric disorders have seriously affected human life, one of the risk genes related to psychosis is the methylenetetrahydrofolatereductase (MTHFR) gene. This gene has a potential role in psychiatric disorders. Therefore, a meta-analysis is conducted to investigate the correlations between two prevalent MTHFR single nucleotide polymorphisms (SNPs), MTHFR C677T, A1298C, severe psychological disorders (schizophrenia, major depression, bipolar disorder).MethodsA total of 81 published studies were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…MTHFR A222V has been linked to an increased risk of bipolar disorder in the recessive model (TT vs. CT + CC). Ethnic subgroup analysis shows that schizophrenia for T vs. C: OR = 1.19, 95% CI = 1.11-1.29, P < 0.001; for TT + CT vs. CC: OR = 1.22, 95% CI = 1.10-1.35, P < 0.001; for TT vs. CT + CC: OR = 1.31, 95% CI = 1.16-1.48, P < 0.001; for TT vs. CC: = 1.46, 95% CI = 1.24-1.72, P < 0.001 and major depression for T vs. C: OR = 1.46, 95% CI = 1.21-1.77, P < 0.001; for TT + CT vs. CC: OR = 1.52, 95% CI = 1.11-2.08, P = 0.009; for TT vs. CT + CC: OR = 1.75, 95% CI = 1.34-2.28, P < 0.001; for TT vs. CC: OR = 1.89, 95% CI = 1.40-2.57, P < 0.001 significantly correlate with MTHFR A222V in Asian populations (Zhang et al, 2022).…”
Section: Instrument To Assess Misconception Levelsmentioning
confidence: 90%
See 1 more Smart Citation
“…MTHFR A222V has been linked to an increased risk of bipolar disorder in the recessive model (TT vs. CT + CC). Ethnic subgroup analysis shows that schizophrenia for T vs. C: OR = 1.19, 95% CI = 1.11-1.29, P < 0.001; for TT + CT vs. CC: OR = 1.22, 95% CI = 1.10-1.35, P < 0.001; for TT vs. CT + CC: OR = 1.31, 95% CI = 1.16-1.48, P < 0.001; for TT vs. CC: = 1.46, 95% CI = 1.24-1.72, P < 0.001 and major depression for T vs. C: OR = 1.46, 95% CI = 1.21-1.77, P < 0.001; for TT + CT vs. CC: OR = 1.52, 95% CI = 1.11-2.08, P = 0.009; for TT vs. CT + CC: OR = 1.75, 95% CI = 1.34-2.28, P < 0.001; for TT vs. CC: OR = 1.89, 95% CI = 1.40-2.57, P < 0.001 significantly correlate with MTHFR A222V in Asian populations (Zhang et al, 2022).…”
Section: Instrument To Assess Misconception Levelsmentioning
confidence: 90%
“…The relationship between the MTHFR A222V polymorphism and disease might be associated with two aspects involving homocysteine concentration and altered metabolism of folates and homocysteine (Ueland et al, 2001). The disease that might be involved such as diabetic neuropathy (Wu et al, 2017;Yigit et al, 2013), congenital heart disease (CHD) (Xuan et al, 2014), renal failure (Hishida et al, 2013), cancer (He et al, 2017;Kumar et al, 2018;Li et al, 2021), psychiatric disorders (Zhang et al, 2022), etc. This genetic variation requires further exploration regarding the risk of changes in protein structure and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Genetics, epigenetics, neuroactive molecules, psychiatric history, social support, heath history, use of substances, and adverse life events belong under this branch. Regarding genetics, DNA is an essential baseline for the possible development of diseases [11]. Recent research has shown that 49% of individuals diagnosed with PPP have a history of BD [11].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Regarding genetics, DNA is an essential baseline for the possible development of diseases [11]. Recent research has shown that 49% of individuals diagnosed with PPP have a history of BD [11]. In cases of full blood siblings where one sister developed PPP, which was triggered during childbirth, higher chances of PPP development are noted for the other sister compared with the rate of occurrence in non-related individuals [12].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Folates, the main players in C1 metabolism, are essential for monoamine synthesis and genome stability, as they regulate DNA synthesis, repair, and methylation. Dihydrofolate, the form of folate naturally present in our diet ( 3 ), is gradually converted into L-methylfolate in the digestive tract by the methylenetetrahydrofolate reductase (MTHFR), one of the key enzymes of this metabolism ( 4 ), which gene is associated with schizophrenia ( 5 ). L-methylfolate is the main active form of folate available in the body, it crosses the blood-brain barrier and is converted into tetrahydrofolate.…”
Section: Introductionmentioning
confidence: 99%